A Convenient Synthesis of Some New Indole Containing Thiazolidinone, Thiohydantoin, Triazine and its Derivatives with Ethoxyphthalimide Moiety - Hussain, Nasir; Joshi, Ajit; Sharma, Chirag; Talesara, G.L. (Asian Journal of Chemistry, 2012)
Acid catalyzed condensation of thiosemicarbazide with indole-2,3-dione (isatin) yielded indole-2,3-dione-3-thiosemicarbazone (1). 3-[(1,3-Thiazolidin-4-one-2-yl)hydrazido]-indole-2-one (2) and 3-[(2-thioxoimidazolidin-4-one-3-yl)imino]-indole-2-one (3) were obtained by condensation of (1) with chloroacetic acid under different conditions. Compounds (2) and (3) on interaction with various aromatic aldehydes afforded the corresponding 5-substituted benzylidene derivatives (4a-d) and (5a-d) respectively, which on refluxing with bromoethoxyphthalimide furnished the corresponding 3-[(5-(4-substitutedbenzylidene)-3-Nethoxyphthalimido-1,3-thiazolidin-4-one-2-yl)hydrazido]-1-N-ethoxyphthalimido-indole-2-one (6a-d) and 3-[(5-(4-substitutedbenzylidene)-2-phthalimidoxyethylsulfanyl-imidazolin-4-one-3-yl)imino]-1-N-ethoxyphthalimido-indole-2-one (7a-d). Compound (1) was also cyclized with KOH in absolute ethanol to yield 2,5-dihydro-3H-[1,2,4]triazino[5,6-b]indole-3-thione (8). Subsequent treatment with bromoethoxyphthalimide yielded 3-(phthalimidoxyethylsulfanyl)-5-N-ethoxyphthalimido-[1,2,4]triazino[5,6-b]indole (9). All the synthesized compounds were characterized by their spectral and elemental analysis data.